Pharmacogenetic profile and major depressive and/or bipolar disorder treatment: a retrospective, cross-sectional study. (12th September 2018) - Tonozzi, Theresa R; Braunstein, Glenn D; Kammesheidt, Anja; Curran, Chris; Golshan, Shahrokh; Kelsoe, John
Aim: To compare pharmacogenetic test predictions with self-reported treatment experience and side effect tolerability among patients with depression taking psychotherapeutic medications.Methods: Subjects completed a survey recalling medication effectiveness and side effects and then underwent pharmacogenetic testing.Results: Our 15 gene pharmacogenetic panel predicted efficacy (p < 0.001) but did not predict side effect tolerability (p = 0.70) in a group of 352 patients. The pharmacogenetic panel and reported efficacy corresponded 60% of the time and medication tolerability agreed 71% of the time.Conclusion: Pharmacogenetic testing may be a useful adjunct to predict efficacy of medications used to treat depression.